Karakterisasi sifat agronomik mutan (m4) padi beras hitam (Oryza sativa L.) yang ditanam pada lahan sawah - Yani, Irmayani; Suliartini, Ni Wayan Sri; Ujianto, Lestari (Jurnal Agrotek Ummat, 2024)
The G10 line and the Baas Selem cultivar were mutated with gamma rays to correct their deficiencies and observed in the first to third generation mutants, then planted again for the fourth generation (M4) but still experiencing segregation. Therefore, research was conducted by characterizing the agronomic properties of black rice in order to obtain superior varieties. This research was conducted in March-November 2023 in Saribaye Village, West Lombok. The method used is an experimental method with a Randomized Block Design (RBD) consisting of 22 treatments with 3 replications, namely 20 mutant genotypes (10 Baas Selem mutants and 10 G10 lines). This research starts from the nursery, transplanting, maintenance to harvest. The results of the study showed that there were differences in the quantitative characteristics of the mutant (M4) of black rice (Baas Selem Mutant and G10 line) with the comparison plants (SP Control and Inpari-32) in terms of plant height, total number of tillers, panicle length, number of filled grains per panicle, number of empty grains per panicle, and weight of grain per hill. The G10 mutant line in the G18 genotype was superior in the characters of panicle length (28.46 cm), number of filled grains per panicle (169.60 grains), and weight of filled grain per hill (49.63 grams). The G10 mutant line in the G18 genotype was superior in panicle length (28.46 cm), number of filled grains per panicle (169.60 grains), and weight of filled grains per clump (49.63 grams).